Integrating Early and Late-Phase Requirements: A Factory Case Study - Alencar, Fernanda Maria Ribeiro de; Castro, Jaelson F. Brelaz (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1999: Anais do XIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1999.23913, 1999)
Requirements Engineering (RE) is getting more attention as it has been recognized as a crucial phase in the development of the software system life cycle. Recent works have made a distinction between early-phase RE and later-phase RE. Early-phases RE activities are typically informal and addresses non-functional requirements. The later-phase RE usually focuses on completeness, consistency, and automated verification of requirements. In this paper, we show how early and late requirements specifications can be integrated. For the organization modeling we use the i* technique [1], which allows a better description of the organizational relationships among the various agents of a system as well as an understanding of the rationale of the decisions taken. For the formal functional specification of the requirements, we use Structured Modal Action Logic - MAL [2]. Some guidelines are presented for the integration of the two phases. Throughout the paper, we make use of a mineral water factory as an example, to describe the approach.